A Study of Tradition Pa Oua Pakar in Khanadmon Sub-district, Sangkha District, Surin Province - Intrakamheang, Phatra; Sipachai, Laddawal (Academic MCU Buriram Journal, 2019)
The research found that Pa Oua Pakar tradition Schedule ceremony held on 12th lunar month every year (the 15th lunar month 12), which corresponds to Loykrathong. In the pre-season and into the next year’s crop. The community is home to the Mon-sized farming community from their ancestors. The predicted rain rituals to prepare and plan the cultivation according to the prediction, and activities related to Buddhism. Tradition and recreation of merit charity dedicated to fathers who have passed away. This ritual art Pa Oua Pakar tradition creates a social community relations affect the lifestyle of residents in adhering to the moral. The efforts in philanthropy and unity in the community. Guidelines for the Conservation Pa Oua Pakar tradition is involvement of the community, to raise awareness values of the people in the community, reconstruction and development activities to practice or dissolved, and improving tourist attractions in the vicinity, and sales of products that are unique to the community. The guidelines published there should be a public relations activities of the community. The preparation of the working group. Preparation activities as well as the cooperation of citizens to undertake activities to promote sustainable tourism.